Juan Diego, modelo indígena de santidade branca: representação, sincretismo e identidade no México do século XVII - Souza, Leandro Faria de (2014)
This paper aims to discuss the way in which the representation of indigenous Juan Diego is being drafted by the works of Miguel Sánchez, Luis Lasso de la Vega and Luis Becerra Tanco, published in 1648, 1649 and 1666, respectively, to determine this character as a typical white sanctity of the seventeenth century in order to maintain the tradition of Our Lady of Guadalupe as an example of syncretism and religious identity Mexican style